2021
DOI: 10.1186/s40729-021-00342-x
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory performances and maximum occlusal forces of immediate and conventional loaded two-implant supported overdentures retained by magnetic attachments: preliminary study of randomized controlled clinical trial

Abstract: Background The appropriate loading protocol to improve masticatory performance (MP) is still unclear in elderly patients and two-implant overdentures (2-IODs) wearers. This study aimed to compare the long-term MP and maximum occlusal force of immediate loading (IL) and conventional loading (CL) of 2-IODs retained by magnetic attachments. Nineteen edentulous patients were randomly assigned to either an IL (n=10) or CL group (n = 9). In the IL group, the implant was loaded on the same day as inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…4 masticatory efficiency. Besides, the average number of strokes required to swallow was more than 40 (19) . It was asserted that masticatory efficiency was improved by retention and stability attained by implant overdentures.…”
Section: Discussionmentioning
confidence: 99%
“…4 masticatory efficiency. Besides, the average number of strokes required to swallow was more than 40 (19) . It was asserted that masticatory efficiency was improved by retention and stability attained by implant overdentures.…”
Section: Discussionmentioning
confidence: 99%
“…Table (2) and Fig. (6) revealed that the retentive forces of indirect incorporation of TITACH attachment at measurement times. It showed statistically significant higher mean retention values (P≤0.001*).…”
Section: Table (1) and Fig (6) Revealed That Retentive Forces Of Dire...mentioning
confidence: 92%
“…Thus, two-implant overdentures should be considered a possible alternative treatment for patients with edentulous mandibles. (6) In general, Overdentures supported by two implants show more patient satisfaction than overdentures supported by more than two implants. Implant supported overdenture therapy had improved masticatory efficiency, bite force, thickness of masseter muscle, in addition to functional and psycho-social improvements.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation